PMSG-based Wind Turbine Torque Harmonic Reduction Through LPV Control of EKF-Based Disturbance Estimation. Issue 28 (2019) - Salameh, Jack P.; Cauet, Sebastien; Etien, Erik; Sakout, Anas; Rambault, Laurent
Abstract: Torque disturbance is imposed by the non-stationary wind profile, tower shadow, and wind shear propagate along the drive train to reach wind turbine generators. This is the main cause of several detrimental effects to several mechanical components specifically bearings, gearboxes, drive train, generators, etc. This paper applies Linear Parameter Varying (LPV) control technique based on harmonic estimation and torque reconstruction using the Extended Kalman filter for wind turbine torque ripple cancellation.